Blood pressure response in exercise is associated with future cardiac structural alterations in hypertensive patients. (25th November 2020) - Andrikou, E; Dimitriadis, K; Andrikou, I; Kasiakogias, A; Tatakis, F; Dimitriadi, M; Anastasiou, A; Kintis, K; Kalos, T; Iliakis, P; Tousoulis, D; Tsioufis, C
Abstract: Background/Introduction: Exaggerated blood pressure response (EBPR) during the exercise treadmill test (ETT) is often observed in individuals without known cardiovascular disease. Although it is generally considered as an abnormal response and a risk factor for hypertension development, its clinical significance remains controversial. On the other hand, regression of left ventricular hypertrophy (LVH) is independently associated with improved cardiovascular outcome. Purpose: In this study we aimed to investigate the role of EBPR during exercise in LVH regression in hypertensive subjects over time. Methods: 1413 hypertensive subjects, (mean age 57±11 years), 51% males, with baseline office blood pressure (BP) 144/89mmHg were followed for a mean period of 6.4±3.0 years. At baseline and last follow-up visit all patients underwent office BP, laboratory tests and echocardiographical determination of left ventricular mass index (LVMI). At baseline, all subjects underwent treadmill exercise testing (Bruce protocol) in order to identify the presence of EBPR based on the systolic BP elevation at peak exercise (> or =210 mmHg for men and > or =190 mmHg for women). Main outcome variable was LVH Regression/prevention (LVH Regr/prev), defined as: LVH at baseline visit with normal LVMI values at last visit or absence of LVH at baseline and last visit. BP control was considered optimal when the mean of office BP measurements during follow-up was <140/90mmHg. Results: 46% of study population presented LVH Regr/prev during follow-up period. Cox-regression analysis, after adjustment for clinical and biochemical variables, revealed that low levels of baseline LVMI (HR=0.98, 95% CI 0.97–0.99, p<0.0001), absence of EBPR (HR=0.81, 95% CI 0.67–0.98, p=0.02) and optimal BP control during follow-up (HR=1.19, 95% CI 1.01–1.56, p=0.03) were independent predictors of LVH Regr/prev during follow-up. Conclusions: Beyond optimal BP control, EBPR is a significant predictor of left ventricular mass changes overtime. Hence, ETT can provide clinical relevant information, including EBPR, which may help in the improvement of risk stratification of hypertensive subjects. Funding Acknowledgement: Type of funding source: None